Pembinaan Kemandirian Di Lapas Kelas IIA Purwokerto Ciptakan Life Skill Narapidana - Firsty Aulia Oryza Sativa; Padmono Wibowo (International Forum of Researchers and Lecturers, 2023)
The development of self-reliance is of utmost importance for inmates within the prison environment. Furthermore, it serves to instill awareness in inmates, preventing them from repeating their transgressions and violations of the law, and aiding their reintegration into society upon their release by utilizing life skills acquired while in prison. The research method employed in this study is of a qualitative nature. The self-reliance development program for creating life skills among inmates at Class IIA Purwokerto Prison includes collaborating with Vocational Training Center (BLK) officers, the Department of Fisheries and Animal Husbandry, as well as the Department of Agriculture and Food Resilience. These parties provide specialized training materials in their respective fields. The training materials offered to inmates encompass topics such as agribusiness, animal husbandry, and barbershop skills. The hindering factors that make this process challenging and less effective are primarily rooted in the individual motivations of the inmates, as they may lack the drive to fully engage in the self-reliance development program.